Glutamate metabotropic receptor 4 in breast cancer: a potential and specific target for chimeric antigen receptor therapy - Xu, Yien; Hayierhan, Ayidana; Chen, Zexiao; Ma, Yumei; Zhang, Wenjun; Xu, Chaoliang; Mei, Ruyi; Zhou, Xiaoling; Zhu, Yuhao; Sun, Pingnan; Wu, Jundong (Frontiers in Oncology, 2026)
BackgroundDespite the revolutionary success of chimeric antigen receptor (CAR) therapy in hematologic malignancies, its application in solid tumors is hindered by the scarcity of tumor-specific membrane antigens rigorously validated in clinical specimens. Here, we identified glutamate metabotropic receptor 4 (GRM4) as a novel target with dual advantages: breast cancer (BC)-predominant membrane expression and restricted normal tissue distribution, potentially circumventing on-target off-tumor toxicity.MethodsThrough integrative multi-database analysis (DESeq2/edgeR/limma differential screening, CellMarker filtration, the Human Protein Atlas database validation), GRM4 was prioritized. Its expression was validated in non-malignant organs [immunohistochemistry (IHC)], BC cell lines [western blot (WB)/quantitative polymerase chain reaction (qPCR)/immunofluorescence (IF)], 158 BC clinical samples with paired para-cancerous tissues (IHC). Subcellular localization, tumor proportion score, and subtype-specific distribution were analyzed. Clinical correlations and survival outcomes were evaluated using chi-square tests and Kaplan-Meier analysis.ResultsMembrane expression was confirmed by IHC in 35.44% of clinical cases, and its presence in breast cancer cell lines was validated by WB, qPCR, and IF. GRM4 exhibited tumor-specific membrane/cytoplasmic expression in 80.38% of BC patients (127/158) across all subtypes (≥70% positivity), with 51.27% showing >50% tumor cell positivity. Critically, GRM4 was absent in normal breast/para-cancerous tissues and confined to the brain in non-malignant organs. While GRM4 correlated with advanced clinical stage (p=0.025) and age (p=0.026), it was independent of overall survival (p=0.449).ConclusionsGRM4 emerges as a novel CAR-associated target for breast cancer, demonstrating tumor-specific overexpression, brain-restricted normal expression, and pan-subtype applicability with potential on-target off-tumor effect.